Regulatory Incentives for Innovation: The FDA's Breakthrough Therapy Designation - Chandra, Amitabh; Kao, Jennifer; Miller, Kathleen L.; Stern, Ariel D. (The Review of Economics and Statistics, 2026)
Abstract Regulators of new products confront a trade-off between speeding a product to market and collecting additional product quality information. The FDA's Breakthrough Therapy Designation (BTD) provides an opportunity to understand if regulators can use new policy to innovate around this trade-off. We find that the BTD program shortened clinical development times by 23% and did not affect the ex post safety profile of drugs with the designation. The BTD program had the greatest impact on less experienced firms and reduced clinical trial design complexity. The results suggest that targeted regulatory innovation can shorten R&D periods without compromising product quality.